Generalized tetanus in a landscaper without obvious wounds - Sivasubramanian, Geetha (IDCases, 2020)
Tetanus is rare and potentially fatal infection in the US. Its incidence has declined dramatically over the years in developed countries due to robust immunization programs. We describe a case of generalized tetanus in a 66-year-old inadequately vaccinated landscaper who presented with classical symptoms but did not have any open wounds leading to delay in initial diagnosis but was successfully managed once the diagnosis was established.